Prognostic impact of monocyte count at presentation in mantle cell lymphoma. (29th June 2013) - Aprile von Hohenstaufen, Kathrin; Conconi, Annarita; de Campos, Cassio Polpo; Franceschetti, Silvia; Bertoni, Francesco; Margiotta Casaluci, Gloria; Stathis, Anastasios; Ghielmini, Michele; Stussi, Georg; Cavalli, Franco; Gaidano, Gianluca; Zucca, Emanuele
Summary: An increased number of circulating monocytes at presentation has recently been associated with shorter survival in Hodgkin lymphoma, follicular lymphoma and diffuse large B cell lymphoma. This study aimed to assess the prognostic impact of the absolute monocyte count (AMC) at diagnosis in mantle cell lymphoma (MCL). AMC at diagnosis was available in 97 MCL cases recorded in the databases of the Oncology Institute of Southern Switzerland in Bellinzona (Switzerland) and the Division of Haematology of the Amedeo Avogadro University of Eastern Piedmont in Novara (Italy). With a median follow up of 7 years, the 5‐year overall survival was 29% for patients with AMC >0·50 × 10 9 /l and 62% for patients with AMC ≤0·50 × 10 9 /l ( P  =   0·008). Elevated AMC and beta‐2 microglobulin at diagnosis remained independent outcome predictors at multivariate analysis, controlling for the MCL International Prognostic Index (MIPI), and have been used to build a simple prognostic scoring system. In this relatively small and heterogeneous series an increased AMC identified poor‐risk patients. Our results suggest that AMC together with the beta‐2 microglobulin level might provide an inexpensive way to stratify MCL patient risk as a complement to the MIPI, which was confirmed to be a very powerful prognostic tool.